Effects of Different Beverages on Endurance Performance and Metabolism in Ambitious Recreational Runners Einfluss verschiedener Getränke auf Ausdauerleistung und Stoffwechsel bei ambitionierten Freizeitläufern - Reljic, Dejan; Jost, J.; Friedmann-Bette, B. (Deutsche Zeitschrift für Sportmedizin, 2011)
The present study examined the effects of the sports drinks Caps® (C; low-glycemic, fruit sweetener/wheat dextrin), Gerolsteiner Sport® (G; low-glycemic, fruit sweetener) and Powerade® (P; higher-glycemic, glucose/maltodextrin) compared to an apple juice/mineral water mixture (A) and plain mineral water (W) on performance and metabolic responses during prolonged treadmill-running at 90% of individual lactate-threshold until exhaustion. In a randomized double-blind design, 34 recreational runners received 250ml of each beverage 30 minutes before the onset and after 30 and 60 minutes of exercise. Total-carbohydrate ingestions were: C: 36g, G: 31g, P: 42g and A: 51g, respectively. Capillary blood samples were obtained to determine blood glucose, lactate and ammonia concentrations before and during exercise and rates of perceived exertion were collected. Ingestion of C (79.7±11.7 min.) resulted in a significantly longer time to exhaustion compared to W (72.1±12.8 min.; p<0.01) and P (73.6±18.1 min.; p<0.05). After ingestion of C, G, P and A before the onset and after 45 minutes of exercise, blood glucose levels were significantly higher compared to W. After 60 minutes of exercise, glucose concentrations were significantly higher with C compared to P and A (93,4±11,4 vs. 88,4±11,0 vs. 87,8±10,3 mg/dl; p<0.05). Moreover, ingestion of C led to substantially lower ammonia values during exercise and subjects reported lower ratings of perceived exertion compared to W, G and P. Apparently, the ingestion of a carbohydrate-combination consisting of fruit sweetener and wheat dextrin may optimize energy delivery during exhaustive endurance exercise.
CRIS-Team Scopus Importer:2022-10-11
Keywords: Carbohydrate composition; Endurance capacity; Exercise metabolism; Glycemic index; Sports drinks